De-professionalism and austerity : challenges for the public sector - Malin, Nigel (Policy Press, 2020)
From scarcer resources to greater stresses, this book charts how policies and cuts have compromised workers' ability to undertake their professional roles. Combining research and practice experience, it assesses the extent of de-professionalisation in recent years, and how workers have responded